Enhanced removal performance for Congo red by coal-series kaolin with acid treatment. Issue 10 (29th April 2021) - Niu, Sanxin; Xie, Xiaokang; Wang, Zheng; Zheng, Linhui; Gao, Feng; Miao, Yang
ABSTRACT: In this study, acid treatment coal-series kaolin (AK) materials (named 2AK, 3AK, 5AK, 10AK) were synthesized by a facile method. Batch adsorption experiments were carried out using Congo red (CR) as a model dye pollutant in various experimental conditions. The samples were studied by XRF, XRD, FTIR, SEM, Zeta potential and N2 adsorption techniques. The results indicate that the acid treatment materials exhibit increased specific surface area and pore structures, and showed obvious effects on the adsorption performance of kaolin. Owing to the structural edges of kaolin receiving protons from the hydrochloric acid aqueous solution, the prepared 5AK exhibited excellent adsorption performance for Congo red (CR) anionic dye. The adsorption process followed a pseudo-second-order rate model and the Langmuir isotherm was found a better fit with a maximum adsorption capacity of 237.53 mg/g, which is very close to the experimental data. Thermodynamic studies showed Congo red adsorption on samples was exothermic and spontaneous in nature. The acid treatment coal-series kaolin shows significant potential applications in the fields of adsorption, pH-responsive delivery and other environmental remediation. GRAPHICAL ABSTRACT: